Expression of apoptotic and cell proliferation regulatory proteins in keratoacanthomas and squamous cell carcinomas of the skin - Ribeiro, Daniel; Narikawa, Silvia [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2008)
The aim of this study was to investigate the expression of p53, caspase-3, bcl-2, MIB-1, and PCNA to validate more objective methods to differentiate squamous cell carcinoma and keratoacanthoma, as well as to understand their pathogenesis with accuracy. A total of 52 cases of histopathologically diagnosed keratoacanthoma in the proliferative stage and 56 cases of well-differentiated squamous cell carcinoma were selected in this study. The expression was evaluated by means of immunohistochemistry. Bcl-2 immunoreactivity was weak or absent in the majority of cases, either in squamous cell carcinoma or in keratoacanthoma. PCNA-positive cells did not show differences between two lesions evaluated. on the other hand, MIB-1 was statistically significant (p<0.05) between squamous cell carcinomas and keratoacanthomas. Moreover, p53 and caspase-3 were overexpressed in squamous cell carcinomas. Together, these results suggest that the biological behavior of the well-differentiated squanous cell carcinomas of the skin may be associated with cellular proliferation and/or deregulation of cell death, indicated by increased expression of the MIB-1 and apoptotic proteins p53 and caspase-3, respectively. (C) 2007 Elsevier GrnbH. All rights reserved.
Keywords: keratoacanthoma; squamous cell carcinoma; cell proliferation; apoptosis